How is the basics of marketing e-module developed in vocational high schools? - Lailiyah, Faridatul; Marlena, Novi (Faculty of Engineering, Universitas Negeri Yogyakarta, 2024)
The development of information and communication technology has driven progress in the development of e-module teaching materials. This study aims to determine; 1) e-module feasibility; 2) the effectiveness of the e-module assisted by sigil software. The research model used is the ADDIE R&D model (Analyze, Design, Development, Implementation, Evaluation) by (Branch, 2009) . The subjects of this research were students in class X Digital Business 2 at school Intermediate Vocational (SMK). Expert review and validation sheets, and pretest and posttest question sheets are the instrument used. Evaluation data from experts has been analyzed descriptively qualitatively, while validation by experts has been analyzed using percentages and testing product effectiveness using the N-Gain value formula. The research results show that; 1) e-module assisted by sigil software in element 3 of phase E of the basics of marketing class X subject was declared very feasible by experts with a validation result score of 94.45%; 2) the effectiveness test obtained an N-Gain value of 0.73 in the high effectiveness category, so e-modules are feasible and effective to be used as teaching materials in the process of learning the basics of marketing